Curcumin Nanofibers for Effective Treatment of Diabetic Foot Ulcer: Formulation Development - Naga Aparna, Tatapudi; Padiyar, Anirudh; Singh, Gurinderdeep; Chandrakantbhai Vaghela, Mausami; Bhagat Patil, Arvind R.; Bairagi, Shriram; Kailaspati Prabhakar, Chittam (Journal of Neonatal Surgery, 2025)
Diabetes often causes wounds to heal more slowly and to worsen over time, leading to diabetic wounds or diabetic foot ulcers. With increase in cases of diabetic patients, the number of patients with diabetic wounds is also increasing. In research for the treatment of these wounds, nanofibers and nanogels are observed to be one of the effective ways to cure diabetic wounds. Curcumin was also found to be effective in lowering inflammation and fastening the healing rate. Aim of present research was to formulate curcumin nanofibers with collagen originated from fish. Drug permeation study suggested highest release pattern of F4 nanofiber with maximum amount of collagen content. Further, kinetic studies revealed that n value was less than 0.45 which means diffusion and permeation mechanisms followed. Optimized nanofiber showed antibacterial and antioxidant activity due to presence of curcumin extract. It is anticipated that nanofiber with regulated curcumin release capabilities would be considered as a possible treatment option for diabetic foot ulcers.